Hubungan kepuasan komunikasi dengan komitmen terhadap organisasi di kalangan pekerja teknikal: kajian kes di Flextronics International, Senai, Johor - Mohd. Ariff, Lily Suriani; Ungku Ahmad, Ungku Norulkamar; Abdul Rahman, Siti Aisyah (Faculty of Management and Human Resource Development, 2004)
The aim of this study is to investigate the relationship between communication satisfaction and organizational commitment among technical employees at Flextronics International, Senai, Johor. The objectives of this study are to identify the level of communication satisfaction and organizational commitment, to determine the relationship between communication satisfaction and organizational commitment, to identify the factors that most influenced the organizational commitment and to examine the differences of communication satisfaction and organizational level based on the demographics. Communication Audit Questionnaire (Down and Hazen, 1990) and Organizational Commitment Questionnaire (Mowday, Porter and Steer, 1982) were used in collecting the data. The total of respondents involved in this study is 132. The result reveals that there is positive significant relationship between organizational commitment and communication satisfaction. From the multiple regression analysis, the dimensions of communication satisfaction that most influenced organizational commitment are supervisory communication and personal feedback. In addition, it is found that there exist a significant difference of communication satisfaction level based on race and marital status. As for the organizational commitment level, only marital status found to be significantly different.